Capacity of self-care and family support perceived by persons post infarto acudo de miocardio, Almanzor Aguinaga Asenjo National Hospital, Chiclayo 2019 - Cabrera Delgado, Cinthia Lucero (2021)
Objective: Determine the relationship between the capacity for self-care and the family support perceived by people after acute myocardial infarction (AMI), Hospital Nacional Almanzor Aguinaga Asenjo. Chiclayo, 2019. Method: Quantitative correlational study. The population consisted of 410 people whose sample was 199 people who attended the outpatient cardiology consultation after one year of having suffered an AMI, the non-probability sampling for convenience. Data was collected with the Scale to estimate self-care abilities and the Perception of family support questionnaire. The information was processed with descriptive statistics, drawing up frequency tables and graphs. The measurement of the relationship of the variables was carried out with the Spearman Correlation Coefficient. Ethical criteria and scientific rigor were considered. Main Results: There is a relationship between self-care and family support capacities in the studied population, so the null hypothesis is rejected, demonstrating a linear relationship; and the correlation is very good and directly proportional (rs = 0.825) with bilateral significance (p = 0.01). Overall conclusion: The more family support the post-AMI people present, the better their self-care capacities will be, since the family acts as a stimulus for improvement for people, translating into greater motivation, unconcern and willingness to carry out the necessary care to get out of the clinical picture not to repeat it again, increasing your biopsycho-emotional well-being.